2014
DOI: 10.1016/j.csda.2014.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Nonparametric estimation of the conditional tail index and extreme quantiles under random censoring

Abstract: 23International audienceIn this paper, we investigate the estimation of the tail index and extreme quantiles of a heavy-tailed distribution when some covariate information is available and the data are randomly right-censored. We construct several estimators by combining a moving-window technique (for tackling the covariate information) and the inverse probability-of-censoring weighting method, and we establish their asymptotic normality. A comprehensive simulation study is conducted to evaluate the finite-sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 31 publications
1
31
2
Order By: Relevance
“…Overall, we found that the performance of estimators depend on the distribution, the number of top order statistics and the percentage of censoring. Contrary to what was reported in Ndao et al (2014), we found that the Hill estimator has large bias and MSE except for samples generated from the Fréchet distribution. The proposed PPD estimator is universally competitive in estimating γ 1 (x) regardless of its size, percentage of censoring and number of top order statistics.…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…Overall, we found that the performance of estimators depend on the distribution, the number of top order statistics and the percentage of censoring. Contrary to what was reported in Ndao et al (2014), we found that the Hill estimator has large bias and MSE except for samples generated from the Fréchet distribution. The proposed PPD estimator is universally competitive in estimating γ 1 (x) regardless of its size, percentage of censoring and number of top order statistics.…”
Section: Resultscontrasting
confidence: 99%
“…The existing estimators result from the application of the moving window technique (Gardes and Girard, 2008) and the inverse probability-of-censoring weighted method (Beirlant et al, 2007;Einmahl et al, 2008) to adapt classical estimators to censoring. Ndao et al (2014) used this approach to adapt the Hill, generalised Hill and moment estimators to censoring. In this section, we review these estimators and follow a similar approach to propose other estimators of the extreme value index in the next section.…”
Section: The Existing Estimatorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Matthys et al (2004), Beirlant et al (2007) and Einmahl et al (2008) additionally address estimation of extreme quantiles. Ndao et al (2014) address estimation of the conditional extreme-value index and conditional extreme quantiles with fixed covariates and censoring. To our knowledge, estimation of the conditional extreme-value index and extreme quantiles with random covariates and censoring has not yet been addressed.…”
Section: Introductionmentioning
confidence: 99%